The role of the National Agency for the Support and Employment of Youth in supporting the establishment and accompanying women entrepreneurs - Belhiani, Khadidja; Eliaselhannan, Farah; Redjimi, Sarra (Finance and Business Economies Review, 2019)
This study aims to evaluate the experience of the National Agency for Youth Support and Employment (ANSEJ) in the field of accompanying and establishing women entrepreneurs in order to improve the services it provides to promote this sector, which will benefit national development and the economy. The study found that the agency under study was relatively successful in view of the percentage of established women's institutions and the number of women's jobs they provided, but did not rise to the desired level, and it remains as a modern experiment far from the level reached by many neighboring countries, Obstacles to strengthening the prospects for their participation.